Molecular genetic analysis reveals that a nonribosomal peptide synthetase-like (NRPS-like) gene in Aspergillus nidulans is responsible for microperfuranone biosynthesis - Yeh, Hsu-Hua; Chiang, Yi-Ming; Entwistle, Ruth; Ahuja, Manmeet; Lee, Kuan-Han; Bruno, Kenneth S.; Wu, Tung-Kung; Oakley, Berl R.; Wang, Clay C. C. (Applied microbiology and biotechnology, 2012)
Genome sequencing of Aspergillus species including Aspergillus nidulans has revealed that there are far more secondary metabolite biosynthetic gene clusters than secondary metabolites isolated from these organisms. This implies that these organisms can produce additional secondary metabolites, which have not yet been elucidated. The A . nidulans genome contains 12 nonribosomal peptide synthetase (NRPS), one hybrid polyketide synthase/NRPS, and 14 NRPS-like genes. The only NRPS-like gene in A . nidulans with a known product is tdiA , which is involved in terrequinone A biosynthesis. To attempt to identify the products of these NRPS-like genes, we replaced the native promoters of the NRPS-like genes with the inducible alcohol dehydrogenase ( alcA ) promoter. Our results demonstrated that induction of the single NRPS-like gene AN3396.4 led to the enhanced production of microperfuranone. Furthermore, heterologous expression of AN3396.4 in Aspergillus niger confirmed that only one NRPS-like gene, AN3396.4, is necessary for the production of microperfuranone.